The effect of digital technology on prisoner behavior and reoffending: a natural stepped-wedge design - McDougall, Cynthia (Journal of experimental criminology, 2017)
Although prisons aspire to rehabilitate offenders, they fail to prepare prisoners for release into our modern digitally sophisticated society. The objectives of the current study were to assess the impact of digital technology on the culture of prisons, and on prisoners’ ability to self-manage their behavior and reoffending.